Evicting the undesirables. The idealism of public space and the materialism of the bourgeois State - Bernd Belina (Belgeo)
In political as well as in scientific debates, the concept of “public space” is invoked by both supporters and critics of the eviction of undesirables (beggars, drug addicts, prostitutes) from urban spaces. Both sides use the concept as a codeword standing for opposing interests, both directed at the state. Drawing on Habermas’s conception of the “public sphere”, the paper argues that any such notion of “public space” is necessarily normative and does not help to explain the eviction of undesirables. Instead of this idealism, an analysis of the concrete processes and the interests that drive them is sought. This is done by examining the nature of regulating the access to urban spaces, the rhetoric of “zero tolerance” and the concrete measures of law enforcement applied in various cities in the US and Western Europe. These are shown to be means of the state to control the “reserve army” and thus part and parcel of global social processes.